Akurasi dalam Memprediksi Penetapan Besaran Anggaran Proposal Pendapatan dan Belanja Universitas Menggunakan Metode Monte Carlo - Yogo Turnandes (Jurnal Informatika Ekonomi Bisnis, 2020)
The Institute for Research and Community Service at the University of Lancang Kuning has the mandate in research and service activities which are the two dharmas of the Tri Dharma of Higher Education. The purpose of this study is to predict the determination of the budget amount for the University Income and Expenditure Budget (APBU) proposal approved at LPPM Unilak for the following year. Thus, it will make it easier for the LPPM leadership to make decisions on the acceptance of APBU proposals that are approved quickly and optimally. The data used in this research is APBU research and service proposal data approved in 2018 to 2020 which is processed using the monte carlo method. The APBU proposal budget prediction will be carried out every year. Based on the results of tests that have been carried out with the monte carlo method, it is found that the system used to predict the amount of APBU proposal budget approved in 2019 with an average accuracy of 84% and in 2020 with an average accuracy of 73%. Then with a fairly high level of accuracy, the application of the Monte Carlo method is considered to be able to predict the amount of the APBU proposal budget that is approved by each faculty each year.